(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
Corrosive solution (Hydrochloric acid) has been over and over utilized in manufacturing processes, covering cleaning pickling, acid descaling by acids and oil fully acidize. Inhibition effect of the inhibitor named "2-(((1H-benzo[d]imidazol-2-yl) imino)methyl)phenol" [BIMP] on mild steel in 1 M hydrochloric acid has been scanned employing a technique named weight loss. The results of the study reveal that the inhibition efficiency of BIMP depends on its concentration and attains approximately 81.4% at 0.5 g/L. It is found that the BIMP shows significant action as an inhibitor for mild steel corrosion in corrosive media. BIMP has efficiency raised regarding to temperature decreasing and raising BIMP concentrations.